Mewujudkan Sustainable Development Goals (SDGS) MelaluiSekolah Lapang Terhadap Perkembangan Pengetahuan Petani Kopi Di Desa Hutagurgur, HumbangHasundutan, Sumatera Utara - Ainun Najib; David Ndaru Aji Pramudya; Mirza Andrian syah (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2024)
Coffee has become a promising leading commodity in the North Sumatra region. However, in the practice of coffee cultivation at the location, issues were found where most farming practices did not comply with Good Agriculture Practice (GAP). One way to support the achievement of SDG Goal 8: decent work and economic growth can be through community service. The Edu Farmers International Foundation, through its